The Impact of University Support on Self-Efficacy and Entrepreneurial Intentions: A Mediation Analysis - Hendra Wiyanto; Carunia Mulya Firdausy; Otto Randa Payangan; Haris Maupa; Syarifuddin Sulaiman (Dinasti Publisher, 2024)
Entrepreneurship among students is an important aspect in encouraging innovation and economic development. Recognizing the critical role of university support in shaping students' entrepreneurial journeys, this research explores the complex dynamics between such university support, self-efficacy, and entrepreneurial intentions. In an era where startups contribute significantly to the economy, understanding this relationship is a must for educational institutions. The main objective is to analyze the impact of university support on students' entrepreneurial intentions through the mediating influence of self-efficacy. A comprehensive survey-based methodology will be used to collect data from a diverse sample of private university students in DKI Jakarta. The survey includes validated scales to measure university support, self-efficacy, and entrepreneurial intentions. The statistical technique is structural equation modeling. Preliminary findings reveal significant correlations between university support, self-efficacy, and entrepreneurial intentions. Mediation analysis reveals that university support influences students' entrepreneurial intentions through self-efficacy. This research contributes valuable insights to entrepreneurship education by highlighting the mediating role of self-efficacy in the relationship between university support and entrepreneurial intentions. The results of this research have implications for universities that want to optimize their support systems to foster students with an entrepreneurial spirit, which ultimately encourages innovation.